(untitled) (Eurasian Scientific Herald, 2022)
The article provides practical and theoretical advice on the socio-psychological factors of preparing girls for family life in Uzbek families. The national values and spirituality of Uzbek families are radically different from those of other nations. These factors in our nation are radically different from those of other nationalities in the upbringing of Uzbek girls in our nation. Over the centuries, the importance of preparing our daughters for family life has not lost its relevance in educating them for independent living. The research of foreign and domestic scientists in the field was used to cover the topic of the article. The results from the article can be used as a theoretical recommendation in psychology classes.